"CRIZA CIVILIZAŢIEI" ŞI NICHIFOR CRAINIC STUDIU PRELIMINAR ASUPRA TRADIŢIONALISMULUI INTERBELIC (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
The obsession with the doom of European civilization did not spare Romanian thinkers. I believe that it lays at the foundation of the activity Nichifor Crainic. The solution he put forward was an aesthetic utopia: equating order, goodness and beauty, he called for a cultural policy and a social structure that would respect the principles of stylistic unity, harmony, proportionality, equilibrium, and originality and that should expiate the sins of a fragmented and chaotic world.